TICKETS BOOKING SERVICE AIRCRAFT INFORMATION THROUGH THE INTERNET FACILITIES USING PHP AND MYSQL - R. Hemi Muji Priatna; Fitri Sjafrina, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Currently Raudhah Tourism is still using the traditional management of doingministry. The author therefore tried to create a media to convey and disseminateinformation about products and services. Raudhah tour, about the company profile,schedules -timetables and various services provided by the company in a website.Internet is one means of promotion of transportation alternatives for air travel agents,tour raudhah.To compete in the business world trip air transportation. Website as amedia campaign will provide some value plus the promotional tools withinternational scope that can be accessed by anyone in the world via the internet andcan display a much more complete information with promotional costs are relativelylower compared to other promotional media.